Saving the mill the amazing recovery of one of Japan's largest paper mills following the 2011 earthquake and tsunami - Sasa, Ryoko 1968-; Gonzalez, Tony (Tokyo Japan Publishing Industry Foundation for Culture, 2014)
"On March 11, 2011, one of the largest earthquakes in human history struck offshore of northeast Japan, triggering a massive tsunami that devastated surrounding coastal areas. One of the many victims of this epic disaster was Nippon Paper Industries' Ishinomaki Paper Mill, which was so flooded and covered in debris that it was completely shut down. NPI provided around 40% of the paper used by Japan's publishing industry and its Ishinomaki mill--home to one of the largest paper machines in the world--was its core production facility. Loss of this plant would have been a devastating blow. When the factory's leader Hiromi Kurata announced that the mill would be producing paper again in just six months, few believed him. The city of Ishinomaki still had no power, no gas, and no water. Even finding food and shelter was a challenge for many, and the plant was so covered in debris that large parts were still inaccessible. Even so, the burden of saving their company, their city, and even the Japanese publishing industry had been placed on the shoulders of the mill's employees. Their story is a monument to the indomitable spirit of the Japanese worker." -- Publisher's description.
Originally published in Japanese: Kami tsunage! karera ga hon no kami o tsukutteiru : saisei Nihon Seishi Ishinomaki K?oj?o (Tokyo : Hayakawa Publishing, 2014).
Edition statement from colophon.
Includes bibliographical references (page 199).
In English with parallel title in Japanese.
Keywords: Nihon Seishi Kabushiki Kaisha. -- Ishinomaki K?oj?o.; Paper industry -- Japan; Papermaking -- Japan; Tohoku Earthquake and Tsunami, Japan, 2011.; Disaster relief -- Japan -- T?ohoku Region